Learning Styles and Employee Skills in the Context of Selected Segments of the Labour Market - Sitko-Lutek, Agnieszka; Jakubiak, Monika (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The paper examines learning styles and employee skills at innovative companies. These were evaluated in the context of selected segments of the labour market. The modern labour market may be analyzed using numerous criteria. The focus here was on the division of positions in organizations. The authors sought to determine whether positions occupied by respondents affected their learning styles and skills. The results of the study can be applied by HR managers and specialists in designing human resource management systems that can be adjusted to the needs of employees representing particular position types.The empirical study was conducted by means of a diagnostic survey based on a questionnaire. 1365 employees of innovative companies located in Poland replied and the questionnaires were analyzed with statistical methods. The results enabled recommendations for HR managers and specialists to be formulated. The recommendations pertain to the management of teams in modern enterprises.